Failure analysis of pipeline indents using steel precision balls under subsea conditions. (February 2018) - Gill, W.S.; Marshall, M.B.; Lewis, R.; Hall, B.; Bolton, S.
Abstract: Mechanical connectors used to repair sub-sea pipe lines can use balls to achieve grip on the pipe surface. While designed to indent the pipe surface, it has been found that some balls skid instead which reduces the connection integrity. This work was aimed at finding important features which relate to rolling and skidding of precision balls on the surface of pipes. A skidded ball is associated with a failure and a rolled ball is associated with success. Experiments simulating the activation were performed and compared with analytical models. Several features such as friction, ball size, material hardness and surface finish were identified as important for understanding the transition of the ball from roll into skid. The results of the surface and subsurface analysis correlated well with the model output. Once the important features are verified, progress can be made to achieve production of more robust connectors (from successful activations) leading to better customer confidence in buying mechanical pipeline connector products.